The Influence Of Emotional Intelligence And Organizational Climate On The Performance Of Pamong Praja Police Unit Employees - Helma Laila Putri; Sari Marliani; July Yuliawati (PT. Berkah Digital Teknologi, 2024)
Purpose of the study — This study aims to determine the influence of emotional intelligence and organizational climate on employee performance Research method— The research was carried out at the Karawang Civil Service Police Unit office using a quantitative descriptive verifiative approach with multiple linear regression analysis, employing SPSS V.25 Software. The population consisted of 110 employees, with a sample of 86 employees determined using the Slovin formula. Result The findings indicate: 1) Emotional Intelligence scored 462, categorized as high; 2) Organizational Climate scored 465, also categorized as high; 3) Employee Performance scored 470, categorized as good; 4) Emotional Intelligence has a very significant positive effect on employee performance with a significance value of 0.000 (p < 0.05) and a calculated t-value of 2.413 (t > 1.988); 5) Organizational Climate also positively impacts employee performance with a significance value of 0.000 (p < 0.05) and a calculated t-value of 2.742 (t > 1.988); 6) Both Emotional Intelligence and Organizational Climate have a simultaneous significant effect, with a significance value of 0.000 (p < 0.05) and a calculated F-value of 54.820 (F > 3.107). Conclusion— The determination value was found to be 0.569 (55%), indicating that 45% of the variance in employee performance is influenced by variables not studied in this research.